Injury prevention in football: Knowledge and behaviour of players and availability of medical care in a Nigerian youth football league - Owoeye, OBA; Akinbo, SRA; Olawale, OA; Tella, BA; Ibeabuchi, NM (South African Journal of Sports Medicine, 2013)
Background. Exposure to competitive football is increasing among male youth football players in Nigeria. However, medical support to abate the impact of injuries appears inadequate and there is limited literature to show whether youth football players are knowledgeable about, and practise effective measures for injury prevention in football (IPF). Objective. To assess the knowledge and behaviour of male youth football players regarding IPF and the availability of medical care for players. Methods. We conducted a cross-sectional study among all registered first-division players of a male youth football league in Lagos, Nigeria. Using a self-administered questionnaire, we assessed players’ knowledge regarding IPF, awareness of the Fédération Internationale de Football Association (FIFA) 11+ injury-prevention programme, injury-prevention behaviour and availability of medical attendants during training and competitive matches. Results. The mean age of the players was 18.5 years (standard deviation (SD) ±1.7; range 12 - 19). Their overall mean knowledge score regarding IPF was 4.40 (SD ±1.92) from a total score of 9, with the majority falling into the poor (39.1%) and fair (43.9%) knowledge categories. Most (79.3%) players were not aware of the FIFA 11+ programme. Less than half (40.5%) wore shin guards during training sessions, while 52.5% reported wearing shin guards during matches. Less than two-thirds always warmed up or cooled down at training or matches. About three-quarters (73.1%) and over half (52.1%) reported not having medical attendants working with their teams during matches and training, respectively. Conclusion. There is a clear deficiency in the knowledge and behaviour of injury-prevention measures among Nigerian male youth football players, and adequate medical care is lacking. There is a need for injury-prevention advocacy and implementation of effective interventions to bridge the identified deficiencies in youth football in Nigeria.